An integrative approach to identify sand fly vectors of leishmaniasis in Ethiopia by morphological and molecular techniques - Pareyn, Myrthe; Dvorak, Vit; Halada, Petr; Van Houtte, Natalie; Girma, Nigatu; de Kesel, Wim; Merdekios, Behailu; Massebo, Fekadu; Leirs, Herwig; Volf, Petr (Parasites & vectors, 2020)
BACKGROUND: Ethiopia is affected by human leishmaniasis caused by several Leishmania species and transmitted by a variety of sand fly vectors of the genus Phlebotomus. The sand fly fauna in Ethiopia is highly diverse and some species are closely related and similar in morphology, resulting in difficulties with species identification that requires deployment of molecular techniques. DNA barcoding entails high costs, requires time and lacks reference sequences for many Ethiopian species. Yet, proper species identification is pivotal for epidemiological surveillance as species differ in their actual involvement in transmission cycles. Recently, protein profiling using MALDI-TOF mass spectrometry has been introduced as a promising technique for sand fly identification. METHODS: In our study, we used an integrative taxonomic approach to identify most of the important sand fly vectors of leishmaniasis in Ethiopia, applying three complementary methods: morphological assessment, sequencing analysis of two genetic markers, and MALDI-TOF MS protein profiling. RESULTS: Although morphological assessment resulted in some inconclusive identifications, both DNA- and protein-based techniques performed well, providing a similar hierarchical clustering pattern for the analyzed species. Both methods generated species-specific sequences or protein patterns for all species except for Phlebotomus pedifer and P. longipes, the two presumed vectors of Leishmania aethiopica, suggesting that they may represent a single species, P. longipes Parrot & Martin. All three approaches also revealed that the collected specimens of Adlerius sp. differ from P. (Adlerius) arabicus, the only species of Adlerius currently reported in Ethiopia, and molecular comparisons indicate that it may represent a yet undescribed new species. CONCLUSIONS: Our study uses three complementary taxonomical methods for species identification of taxonomically challenging and yet medically import Ethiopian sand flies. The generated MALDI-TOF MS protein profiles resulted in unambiguous identifications, hence showing suitability of this technique for sand fly species identification. Furthermore, our results contribute to the still inadequate knowledge of the sand fly fauna of Ethiopia, a country severely burdened with human leishmaniasis.
Keywords: Animals; Sand flies; Morphology; Female; MALDI-TOF mass spectrometry; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Insect Vectors; DNA barcoding; ženské pohlaví; druhová specificita; Leishmaniasis; Phlebotomus; leishmanióza; Species Specificity; Psychodidae; Phylogeny; hmyz - vektory; Male; Protein profiling; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Ethiopia; Etiopie; zvířata; mužské pohlaví; fylogeneze